Physicochemical and functional properties of bulla from Ensete ventricosum for food applications - Weyya, Getu; Tadesse, Eneyew; Admassu, Habtamu; Adem, Muhammed (Frontiers in Sustainable Food Systems, 2025)
IntroductionEnset (Ensete ventricosum) is, a perennial crop native to Ethiopia, yields a variety of starch-based foods. It serves as a staple food for approximately 24 million people, which is roughly 20% of the Ethiopian population. This study aimed to investigate the impacts of different parts of Ensete ventricosum and pressing cycles on the proximate composition, functional properties, and mineral content of bulla extracted from the pseudostem and corm, across multiple processing stages.MethodsThe proximate composition including moisture content, ash, fat, fiber, and Crude protein were determined using the official AOAC method 920.87. Carbohydrates were measured according to the method outlined by FAO and World Health Organization, while gross energy content was calculated based on the Atwater conversion factors. The functional properties of bulla extracted from Enset (Ensete ventricosum) such as bulk density, water absorption capacity, oil absorption capacity Swelling power and solubility were also analyzed using different standard analytical methods. Mineral contents were analyzed using Scanning Electron Microscopy (SEM) coupled with Energy-Dispersive X-Ray Spectroscopy (EDS).ResultsThe yield of Bulla from the first, second, and third pressings of the pseudostem was 89.1 grams (25.86%), 20 grams (5.80%), and 14 grams (4.06%), respectively. The proximate composition revealed moisture content ranging from 15.35 to 16.10%, ash content from 0.205 to 0.335%, crude fiber from 0.405 to 0.300%, protein from 0.595 to 0.760%, and carbohydrate content from 0.570 to 0.760%. The functional properties of Bulla, including bulk density (BD), water absorption (WA), solubility index (SI), oil absorption (OA), and swelling power (SWP), ranged from 0.645 ± 0.006 to 0.813 ± 0.009 (g/mL), 1.803 ± 0.077 to 4.413 ± 0.286 (%), 3.100 ± 0.424 to 6.391 ± 0.136 (%), 1.752 ± 0.011 to 2.043 ± 0.003 (mL/g), and 4.945 ± 1.133 to 7.430 ± 0.940, respectively. All values represent the mean ± SD of replicate analyses. The elemental composition of Bulla showed ranges for oxygen from 53.05 to 91.1, sodium from −2.45 to 2.33, magnesium from −0.99 to −0.02, potassium from 0.47 to 4.91, copper from −3.73 to 11.94, zinc from −1.87 to 3.96, selenium from −1.24 to 0.95, calcium from 0.02 to 0.43, and iron from −0.55 to 4.06. All mineral content results are presented in weight% and atomic %.DiscussionThe study revealed significant impacts of enset pressing cycles and fractions on the physicochemical, functional, and mineral composition of bulla derived from the pseudostem and corm of the yeshraqinqey enset plant. The carbohydrates dominate the composition, with moderate levels of fiber, protein, and fat contributing to its functionality as a food stabilizer and thickener. The corm was identified as a rich source of calcium and iron, enhancing its gelling and stabilizing properties, while the pseudostem bulla exhibited high potassium, supporting its viscosity-modifying potential. The pseudostem bulla showed a particular affinity for viscosity enhancement, while the corm-derived bulla excelled in gelling and stabilizing functions. The study contributes to a deeper understanding of the effects of different processing methods on the properties of bulla, paving the way for enhanced utilization of enset Bulla in various food applications.